PERSEDIAAN KEBUTUHAN BAHAN BAKU KOMPONEN PRODUK RUMAH LAMPU DOWNLIGHT (RD) - Yevita Nursyanti (Jurnal Manajemen, 2019)
This research aims to find out how to calculate the supply of raw material requirements for downlight lamp housing products (RD) This research uses the MRP (Material Requirement Planning) Method, using the Silver Meal Technique and EPP Technique (Economic Part Period) to calculate lot size and minimize cost. The results of the study are using the EPP method, which can produce orders with optimal lot size. The total cost generated is Rp.57,034,745, and it is also known that the right re-order point for each reorder. The total cost using the Silver Meal technique is Rp.61,354,371. Therefore, the EPP technique is more economical compared to the Silver Meal technique. Because it has a difference in the total cost of Rp. 4,319,626.